Analysis of Financial Ratios against Lippo Group Company Share Prices - Mangasi Sinurat (Budapest International Research and Critics University, 2021)
The evaluation disposition euphemistic pre-owned is the disposition of qualitative collections and decimal data. patch the collections euphemistic pre-owned is less important data. 1) supported on the consequences of the glance at the investigator terminated that appearance On Equityon Lippo accumulation fellowships are descriptively categorized as high-pitched or in first-class category. It buoy be seen from the Return On Equity (X1) has a substantial chain reaction on inventory expenditures Stock Prices (Y). 2) supported on the consequences of the glance at the investigator concludes that Earning Per Shareon Lippo accumulation fellowships are descriptively categorized as high-pitched or in first-class category. It buoy be seen from the Earning Per Share (X2) changeable has a substantial chain reaction on the Stock Prices (Y). 3) supported on the consequences of the glance at the investigator concludes that the contemporary Ratioon Lippo accumulation fellowships are descriptively categorized as little or not in the first-class category. It buoy be seen from the Current Ratio (X3) has a substantial chain reaction on inventory expenditures (Y). 4) supported on the consequences of the glance at the investigator concludes that totality assets property activity Overon Lippo accumulation fellowships are descriptively categorized as high-pitched or in first-class category. It buoy be seen from the Total Asset Turn Over (X4) has a substantial chain reaction on the Stock Prices (Y). 5) supported on the consequences of the glance at the investigator concludes that the Lippo accumulation corporation is descriptively in a high-pitched compartmentalisation or in a first-class category, so it buoy be terminated that the possibility The one-fifth is accepted, signification that Return On Equity (X1), Earning Per Share (X2), Current Ratio (X3 Total Asset Turn Over (X4), chalk up a substantial chain reaction simultaneously (simultaneously) on Stock Prices (Y)